Long-latency auditory evoked potentials with verbal and nonverbal stimuli, - Oppitz,Sheila Jacques (2015)
ABSTRACT INTRODUCTION: Long-latency auditory evoked potentials represent the cortical activity related to attention, memory, and auditory discrimination skills. Acoustic signal processing occurs differently between verbal and nonverbal stimuli, influencing the latency and amplitude patterns. OBJECTIVE: To describe the latencies of the cortical potentials P1, N1, P2, N2, and P3, as well as P3 amplitude, with different speech stimuli and tone bursts, and to classify them in the presence and absence of these data. METHODS: A total of 30 subjects with normal hearing were assessed, aged 18-32 years old, matched by gender. Nonverbal stimuli were used (tone burst; 1000 Hz - frequent and 4000 Hz - rare); and verbal (/ba/ - frequent; /ga/, /da/, and /di/ - rare). RESULTS: Considering the component N2 for tone burst, the lowest latency found was 217.45 ms for the BA/DI stimulus; the highest latency found was 256.5 ms. For the P3 component, the shortest latency with tone burst stimuli was 298.7 with BA/GA stimuli, the highest, was 340 ms. For the P3 amplitude, there was no statistically significant difference among the different stimuli. For latencies of components P1, N1, P2, N2, P3, there were no statistical differences among them, regardless of the stimuli used. CONCLUSION: There was a difference in the latency of potentials N2 and P3 among the stimuli employed but no difference was observed for the P3 amplitude.